The Influence of Celebrity Endorser Agnes Monica Towards Perception and Interest to Buy on Honda Vario in Pekanbaru - Irfansyah '; Jushermi '; Aida Nursanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The research is conducted to analyze the influence of Celebrity Endorser Agnes Monica towards Perception and Interest to Buy on Honda Vario in Pekanbaru. There are five variables in this research suchas Credibility (X1), Compatibility (X2), Attractiveness (X3), Perception (Y1) and Interest to Buy (Y2). There are 90 respondents in this study which are with by purposive sampling from all Pekanbaru’s people who do not use Honda Vario yetas total population. Meanwhile qulitatif and quantitative methods are chosen for data analysis by SPSS version 20. The result of this research shows that the variables of Credibility, Compatibility, Attractiveness affect both positively and significantly towards Perception and Interest to Buy on Honda Vario in Pekanbaru. Variables of Credibility, Compability, Attractiveness affect more strength influence towards Interest to Buy on Honda Vario in Pekanbaru after using Moderating Variable, that is Perception Variable.Keywords :Celebrity Endorser, Perception, Interest to Buying.